Pan African phylogeography and palaeodistribution of rousettine fruit bats: Ecogeographic correlation with Pleistocene climate vegetation cycles. (17th July 2019) - Stribna, Tereza; Romportl, Dušan; Demjanovič, Jan; Vogeler, Anna; Tschapka, Marco; Benda, Petr; Horáček, Ivan; Juste, Javier; Goodman, Steven M.; Hulva, Pavel
Abstract: Aim: The impact of Pleistocene climatic oscillations on tropical biomes is associated with changes in the extent of forest cover. Fruit bats have played a role in woodland dynamics via pollination and seed dispersal. We hypothesized that phylogeographic patterns of Rousettus on continental Africa and adjacent islands should show a signature of pluvial‐drought cycles, involving demographic expansions and contractions. Location: Afrotropical, Malagasy and Saharo‐Arabian biogeographic realms. Taxon: Genus Rousettus (Pteropodidae). Methods: Phylogeographic and population genetic approaches using mitochondrial and microsatellite data were integrated with species distribution modelling of currently suitable habitats and those of the Last Glacial Maximum using climate simulations. Results: Phylogenetic reconstruction yielded an Asian outgroup followed by pectinate branching of the Indian Ocean taxa and Rousettus aegyptiacus . While nuclear microsatellites were homogeneous across the African mainland, two mitochondrial haplogroups were found. Haplogroup I is widespread in regions with extensive tree cover, including tropical rain forests, and has close relationships to isolated lineages in the Middle East and islands in the Gulf of Guinea. Haplogroup II is sister to the rest of the R. aegyptiacus radiation and is found in eastern and southern Africa and the Sudanian savanna in habitats with semi‐open land cover. Main Conclusion: Palaeodistributional modelling ascertained that the Indian Ocean islands provided more extensive areas of suitable habitat in the past relative to conditions today, suggesting stepping stone connectivity between Asia and Africa during Pleistocene interpluvial sea‐level lowstands. Inverse pluvial‐drought demography was detected in lineages ancestral to recent haplogroups, providing evidence of past forest refugia and complex ecogeographic scenarios of haplogroup origins involving allopatry and parapatry connected with the eastern Afromontane biodiversity hotspot, and subsequent admixture of nuclear gene pools. The Middle Eastern lineage probably originated during pluvial green Sahara periods, possibly in co‐evolution with ancestors of tree crop species domesticated later during the Neolithic revolution. The keystone role of rousettine bats for forest regeneration and their ability to pioneer dry and distant habitats emphasize their role in conservation biology and restoration ecology.